Assessing the temporal load resolution effect on the photovoltaic energy flows and self-consumption. (May 2021) - Jaszczur, Marek; Hassan, Qusay; Abdulateef, Ammar M.; Abdulateef, Jasim
Abstract: The electrical load temporal resolution on the simulated photovoltaic system electrical energy flows and self-consumption are investigated in order to determine the analysis uncertainty. The renewable energy system under investigation includes a grid-connected photovoltaic system with a capacity of 0.55, 1.1, 1.65, 2.2 and 2.75 kWp. Results show that the load temporal resolution influences the energy flow in the modelled system even for a single household load and a simple photovoltaic system without batteries. It has been found that the household load profile characteristic impact the required data temporal resolution. For high oscillating power, the temporal resolution for the energy consumption of 1 min should be considered, however, if power fluctuations are not high and rapid, a sampling rate of 15 min or even 60 min in most cases is appropriate. The most sensitive parameter for analysis is self-consumption which decreases at high load resolution and increases at low load resolution and may affect instantaneous analysis uncertainty substantially. On average the yearly estimated absolute and relative errors for energy self-consumption in the analysed configuration is 67.33 kWh and 13% at 1.65 kWp photovoltaic system and they decrease with system capacity increase. Finally, two mathematical models are developed and validated for estimation of the relative and absolute errors generated due to the load resolution. Highlights: Household load profile impact required data temporal resolution. Analysis of the influence of temporal load resolution on photovoltaic energy flow. Evaluation of photovoltaic system size and data temporal resolution on self-consumption. Load temporal resolution influenced simulation and system analysis uncertainty.